Application of the Canvas Model in Improving the Entrepreneurship of High School Students - Ety Youhanita; Nur Fithria Wiji Astutik; Kuswanto (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Non-formal education is needed to develop students' hard skills and soft skills in facing the ASEAN Economic Community. This article describes the results of research that aims to analyze the effect of applying the canvas business model in increasing the entrepreneurial spirit of high school students. The subjects of this study were students of class XII with a total of 46 respondents. The research method chosen is descriptive method with a case study approach. Research tools in the form of questionnaires and supporting tools in collecting business model canvas data. While the research method used aims to obtain information, explanations and conditions related to the object of research in a systematic and factually accurate manner. The method to be used is by using a business model canvas approach through interviews and FGD (focus group discussions) conducted on respondents. The conclusion of the research results using the bussines model canvas that students can provide a mature understanding and concept to the community about the business being run.